Digital Strategy and Transformation: Opportunities and Challenges in the Banking Industry in India - Sahoo, Ranjan Kumar (Digital Repository of Theses - SSBM Geneva, 2024)
Digital transformation is becoming a necessity instead of a good-to-have or a luxury. It becomes important as various fintech companies and startups are moving rapidly, taking away customers, creating new white space, or discovering new segments that were once unviable. Various supply-side factors are triggering this rapid change, among them Low cost, ubiquitous internet, 5G speed, the rise of Mobility, and social media, which are triggering direct customer engagement digitally. Also, the rise of India stack, like identity rails like Aadhar and KYC, is causing immediate identification through biometric means, payment rails like UPI and IMPS are triggering immediate buying or transferring money in a secured way, e-sign, PAN validation, OCEN (open credit enablement network), ONDC (open network digital commerce), AA (account aggregator), etc. are helping onboard customers, underwrite them, sign all the documents, and finalize the loan disbursal in a matter of minutes to hours. The state is innovating a lot, which leads to building the foundations for others to leverage and build entrepreneurship. Also, the rise of artificial intelligence, machine learning, and big data analytics is helping to manage credit and market risk quickly. RBI (Reserve Bank of India) regulations are trying to control the growth of credit as it may lead to systemic risks. A small crisis can trigger large-scale delinquencies, threatening the whole banking system. Hence, all these are creating not only new opportunities but also challenges for RE (regulated entities). RBI’s digital lending guidelines are helping streamline and set the overall regulatory landscape for transparency for all players. RBI’s FLDG (First Loss Default Guarantee) will bring innovation in risk underwriting and distribution between fintech and RE players, which will help deepen the credit in the Indian economy help in more entrepreneurship, and production, and create employment opportunities. In this study, we aim to understand the digital strategy, transformation challenges, and opportunities in the Indian banking sector and to develop a framework to address these challenges. The objective of this research is to understand the digital strategy and transformation challenges and opportunities in the Indian banking sector and develop a case study through case study methods.